A content analysis of thematic-integrative, scientific approach, and authentic assessment in the second grade of elementary school textbook theme 6 - Yogi Kuncoro Adi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2017)
The study was detailing: (1) the thematic-integrative content; (2) the scientific approach content; and (3) the authentic assessment content in teacher’s book and student’s book. The study was a content analysis using a qualitative approach. The 2013 Curriculum textbooks for Grade 2 students on the theme of water, earth, and sun which consisted of teacher’s book and student’s book that had been the subject in this study, the thematic-integrative content, the scientific approach content, and the authentic assessment content were the objects in this study. The data analysis technique that had been implemented consisted of unit selection, sample selection, data recording, data reduction, conclusion drawing, and narrative. The results of the study show that: (1) the thematic-integrative contains the aspect of integration and centers on the students’ integration; (2) the use of scientific approach is not always in sequence so that not all indicators in each aspect of scientific approach has been found in each sub-theme; and (3) in terms of authentic assessment content, not all indicators have been found.